We rely on transcutaneous bilirubin in fast paced NICU as compared to serum total bilirubin - Maryam; Talal Waqar; Muneeb Abid; Muhammad Tayyab; Tehreem Fatima; Sidra tul Muntaha (Journal of University Medical & Dental College, 2026)
BACKGROUND & OBJECTIVE: Neonatal hyperbilirubinemia is common and requires timely detection to prevent bilirubin-induced neurological dysfunction. Serum total bilirubin (STB) is the diagnostic gold standard but is invasive and time-consuming, whereas transcutaneous bilirubin (TcB) offers a rapid, non-invasive screening alternative. To evaluate the correlation and agreement between TcB and STB in late preterm and term neonates and to assess the reliability of TcB as a NICU screening tool.METHODOLOGY:It is a Cross-sectional analytical study. A study was conducted at the Neonatal ICU, Combined Military Hospital Kharian, Pakistan, from June to August 2025. A total of 159 jaundiced neonates (35–37 weeks) were included. TcB values obtained with the Dräger JM-105 were compared with simultaneous STB measurements. Data were stratified by gestational and postnatal age. Statistical tests included Shapiro–Wilk, Pearson/Spearman correlation, Intraclass Correlation Coefficient (ICC), and Bland–Altman analysis.RESULTS: Mean TcB was 267.14 ± 77.84 µmol/L, and STB was 276.78 ± 80.12 µmol/L. All subgroups showed strong positive correlations (r/ρ > 0.78, p < 0.01). ICC values ranged from 0.757 to 0.952. Bland–Altman analysis showed a mean bias of –9.64 µmol/L, with limits of agreement from –49.1 to +29.8 µmol/L.CONCLUSIon: TcB demonstrates strong correlation and good agreement with STB and can serve as a reliable screening tool in resource-limited NICUs. However, consistent underestimation and wide limits of agreement limit its use as a stand-alone diagnostic test. STB confirmation is recommended when values approach treatment thresholds.